Towards a New Methodology to evaluate the Urban structure of the Metropolitan Systems; Chicago and Barcelona Metropolitan Areas as Examples. - Blanca Arellano; Montserrat Moix; Josep Roca (European Regional Science Association (ERSA), 2011)
The specialized researches have proposed various approaches to the delimitation of urban and metropolitan systems. Administrative aspects (administrative units historically inherited), morphological (urban continuum), some linked to the economies of agglomeration (population and employment density, urban economic activities, …) or functional interaction (home-work commuting) have been used for the definition of a metropolitan area. At the same time it has developed in recent years, an extensive research that has come to reveal the progressive trend of the metropolitan areas to the polycentrism. There is no doubt that the monocentric city paradigm, structured around a single CBD, is broken. The contemporary metropolises have seen the emergence of the phenomenon of the sub centers. This changes in the internal structure of many cities has extended the hypothesis that the polycentric city is more efficient than traditional monocentric city, from an environmental perspective (ETE, 1999), representing usually shorter home-work trips, thus contributing to more sustainable mobility. However, few efforts have been directed to address the three aspects together: a) the metropolitan boundaries, b) analysis of its internal structure, and c) contrasting the hypothesis of the environmental efficiency of polycentric systems. This paper addresses the challenge of defining an integrated way of both metropolitan areas and their internal composition, structured or not around different sub centers. The methodology developed of the Interaction Value simultaneously allows delimiting these two levels of urban structure: the metropolitan system as a whole and the subsystems articulated around the emerging sub centers, by measuring the functional relationships between housing and workplaces. At the same time, the Interaction Value assesses the degree of polycentrism beyond the simple identification of sub centers developed in the literature. And, so, support the hypothesis that the polycentric city structure is more efficient, from an environmental perspective, than the monocentric. In this way, and taking the cases of Chicago and Barcelona metropolitan areas as examples of these types of organizations, the efficiency of metropolitan structures is evaluated from the dual perspective of land consumption and sustainable mobility.
Keywords: 330